Peningkatan Hasil Belajar Matematika Melalui Model Pembelajaran Kooperatif Tipe Make A-Match Pada Murid Kelas V - musa, habibi (STKIP Andi Matappa Pangkep, 2018)
Abstract. This study aims to determine the improvement of student learning outcomes in mathematics learning through cooperative learning model type make-match in fifth grade students of SD Negeri 3 Wettee, Panca Lautang District, Sidenreng Rappang District. The approach used in this study is qualitative with the Classroom Action Research (Classrom Actioan Research) design. This research was carried out using two variables; that is; Cooperative Learning Model Make A-Match Type and learning outcomes. The subjects in this study were teachers and fifth grade students of SD Negeri 3 Wettee as many as 15 students consisting of 11 male students and 4 female students. Data collection techniques used in this study were observation, tests, and documentation. The data obtained through observations will be analyzed qualitatively. While the learning outcomes obtained by students will be analyzed quantitatively then described systematically so that a conclusion can be obtained. The results showed that the use of the type of cooperative learning model make a-match can improve the mathematics learning outcomes of fifth grade students at SD Negeri 3 Wettee. In addition, the use of the make-a-match cooperative learning model can also increase the activity of students in taking mathematics lessons through collaborative activities in groups.